OPTIMIZATION OF POLYPROPYLENE MEMBRANE SURFACE CHARACTERISTICS THROUGH THE INTEGRATION OF GRAPHENE OXIDE AND IONIC LIQUID BASED ON 1-AMINOPROPYL-3-METHYLIMIDAZOLIUM BROMIDE - Mulyana
Poor adhesion between layers can lead to delamination, where the composite layers in the membrane do not adhere tightly to each other. Instead, separation or detachment occurs between the layers, creating gaps or spaces between them. This can result in structural weakness, reduced resistance to pressure or tension, and even membrane failure at a certain level. The trimethylsilyl groups in the PTMSP structure can interact with the substrate surface or other materials through van der Waals forces and hydrogen bonding, enhancing adhesion. Ionic liquids are organic chemical compounds in a liquid phase composed of cations and anions with unique physical and chemical properties. The aminopropyl group in [APMIM]+ has the potential to form bonds or interactions with functional groups on GO, such as hydroxyl and epoxy groups. This can enhance adhesion between GO and the substrate to be coated. This research focuses on improving the performance of the PP/PTMSP/GO/[APMIM]Br composite membrane through the modification of graphene oxide (GO) and the ionic liquid [APMIM]Br. Preparation was done by making solutions with variations in graphene oxide concentration: 10 mg/mL, 30 mg/mL, and 50 mg/mL. Variations in [APMIM]Br concentration were 2%, 3%, and 5% by weight. The composite with 3 layers, namely PP/PTMSP, PP/PTMSP/GO, and PP/PTMSP/GO/[APMIM]Br, was prepared using the sonication principle. FTIR analysis, SEM, and contact angle tests were conducted to observe the characteristics of the coating membrane. The observed thickness of the PTMSP layer falls within the range of 1-4 ?m, while for GO, it is in the range of 9-11 ?m. Higher concentrations of [APMIM]Br result in increased hydrophilicity, whereas lower concentrations of GO lead to increased hydrophilicity.